Down Syndrome: the benefit of a home programme for children with Down Syndrome as measured on the Griffiths Development Scales - Skenjana, Irene B. Nosiba (My University, 2014)
This study presents the developmental changes in 20 children with Down Syndrome after participating in an early intervention programme (START) for a minimum period of six months, using the Griffiths Development Scales as outcome measures. It is a descriptive 0 ex post facto study comparing developmental change (DQ) in these children with Down Syndrome who participated in the intervention programme with a non-participating or control group matched for age, sex and socio-economic status. All children with Down ° Syndrome were diagnosed clinically and serologically. The data was collected over ten sessions, and included a formal child assessment, using Griffiths,Development Scales, parent or caregivers ,interviews and questionnaires. Analysis indicated that me START programme was associated with a statistically significant improvement in thejdomain o f speech and hearing, and also with the onset of developmental milestones such as sitting, walking and speech: However, there was no statistically significant diffarencdin the ; developmental quotient (DQ) of the two groups. Th^ results were critically examineeiin, terms of methodological issues around acquisition di1 a pure control group pitinBthe ethical imperatives to provide treatment, leading to difficulties in sampli% for age ah d& ree of impairment. From the results it was concluded that the SenAcW have been due to caregiver variations althou^i the START programme may stdl has a role to play.